Diversity of Echinoderms in The Water of Dedap Island, Abang Island Sub-district, Batam City - Sertika Sianipar; Yarsi Effendi; Fenny Agustina (Universitas Labuhanbatu, 2025)
Dedap Island is a group of small islands in the waters off the coast of Abang Island which is famous as a spot for anglers because of its clean location and abundance of marine life. This research is focused on identifying the diversity of Echinoderms in the waters surrounding Dedap Island, located in Abang Island sub-district, Batam City, Indonesia. Additionally, it examines the factors that influence the distribution and abundance of these species. The observation was conducted using line transect methods across various locations, leading to the identification of five species of Echinoderms: three from the class Holothuridae (sea cucumbers), one from the class Astroidea (starfish), and one from the class Echinoidea (sea urchins). The species Diadema setosum (sea urchin) emerged as the most dominant, with a total of 361 individuals recorded. The diversity index (H’) for Echinoderms in Dedap Island was classified as low (0.40), and the evenness index (E) also indicated low values (0.25), suggesting an uneven distribution of individuals and dominance by certain species. Contributing factors to this low diversity include ecological pressures, unstable productivity, and substrate conditions primarily composed of sand